Sistematização das metodologias ESL com enfoque em SystemC - Barbosa, Felipe Sousa (Universidade Federal do Tocantins, 2021)
The present work aim to be a synthesized reference material about Electronic System Level (ESL) methodologies for digital system projects, focus on the use of the C++ library SystemC. There are many methodologies and tools presents in literature that propose solutions for ESL projects. This large amount of material difficulties the decision of which methodologies and tools to use. The SystemC in turn is a IEEE standardized C++ library for hardware projects that allows many design abstraction levels by integrating high-level language and traditional hardware description language functionalities, such as VHDL and Verilog. It has also been integrated in the reference material a study about TLM (Transaction-level Modeling), aiming discuss and present a solution for integration of components in differents level abstractions in a project, thus allowing an early evaluation of the project.